The risks of developing “Do It Yourself (DIY)” music career in unfinished creative city - Wiman Rizkidarajat; Aidatul Chusna; Kholifatus Saadah (Jurnal Sosiologi Dialektika, 2025)
This article endeavors to present findings on the strategic positioning of career development through DIY music by young people as they confront the late capitalism configurations inherent in the creative economy of the provincial city of Purwokerto. Drawing on data collected with a qualitative method, utilizing a biographical approach from October 2022 to January 2025, the study profiles two youth collectives in Purwokerto: Heartcorner Collective and Voicehell. Both employ strategies such as “catch-all” and “non-stop musicians” to advance their careers. However, these strategies fail due to the inadequate development of a comprehensive creative ecosystem in Purwokerto, especially in the music sector. The lack of infrastructure and support leaves DIY musicians struggling to articulate and sustain their careers. This situation places them within the global risk generation, as they navigate the challenges of developing a DIY music career amidst the unfinished creative city framework. Consequently, their efforts to resist established economic patterns and maintain the authenticity of DIY practices become increasingly precarious, reflecting broader issues faced by young people in the creative economy.